Determinants of Economic Growth: The Case of The United States of America - Bakari, Sayef; Tiba, Sofien (Journal of Developing Economies, 2022)
The purpose of this article is to find long- and short-term determinants of U.S. economic growth over the period 1970-2016. By using cointegration analysis and vector error correction models, we compensated for many variables that were not previously linked together. Empirical analysis shows that consumer spending, population, domestic investment, FDI inflows, and exports are long-term sources of economic growth, but FDI outflows, military spending, taxes, and imports are not considered long-term sources of economic growth. grow. In the short run, all variables have no effect on economic growth.